Detection of Salivary Interleukin 2 and Interleukin 6 in Patients With Burning Mouth Syndrome (Hindawi Limited, 2006)
The etiology of BMS remains unknown. Role of various cytokines has been implicated in the development of BMS. The aim of this study was to evaluate levels of salivary IL-2 and IL-6 in patients with BMS, compared with age-matched healthy volunteers (control group). Whole saliva from 30 patients with BMS, age range 55–65, was tested for the presence of IL-6 and IL-2 by enzyme immunoassay. Control group consisted of 30 healthy participants, aged 55–65 years. Saliva IL-2 concentrations in BMS were significantly increased in patients compared to healthy subjects: mean 34.1 ± 9.7 versus 7.3 ± 3.0 pg/mL; <mml:math alttext="$cmathcheck{P<.001}$"> P < .001 . Patients with BMS had significantly higher concentrations of IL-6 compared to control: mean 30.8 ± 5.6 versus 5.2 ± 2.8 pg/mL; <mml:math alttext="$cmathcheck{P<.001}$"> P < .001 . In patients with BMS, IL-2 and IL-6 levels in saliva are elevated, correlating with the severity of illness.